Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

Alternative Expressions of Citizen Voices: The Protest Song and Popular Engagements with the Mozambican State - Manhiça, Anésio; Shankland, Alex; Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Tadros, Mariz (Institute of Development Studies, 2020)
This study examines Mozambican popular music to investigate three questions: Are notions of empowerment and accountability present in popular music in Mozambique? If so, what can these existing notions of empowerment and accountability reveal about relations between citizens and state institutions in general and about citizen-led social and political action in particular? In what ways is popular music used to support citizen mobilisation in Mozambique? The discussion is based on an analysis of 46 protest songs, interviews with musicians, music producers and event promoters as well as field interviews and observations among audiences at selected popular music concerts and public workshops in Maputo city. Secondary data were drawn from radio broadcasts, digital media, and social networks. The songs analysed were widely played in the past two decades (1998–2018), a period in which three different presidents led the country. Our focus is on the protest song, conceived as those musical products that are concerned with public affairs, particularly public policy and how it affects citizens’ social, political and economic life, and the relationship between citizens and the state.
Accepted: 2020-11-02T15:22:47Z ISSN: 2040-0209
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde